"You're Gay, It's Just What Happens": Sexual Minority Men Recounting Experiences of Unwanted Sex in the Era of MeToo. Issue 9 (22nd November 2021) - Gaspar, Mark; Skakoon-Sparling, Shayna; Adam, Barry D.; Brennan, David J.; Lachowsky, Nathan J.; Cox, Joseph; Moore, David; Hart, Trevor A.; Grace, Daniel
ABSTRACT: Our grounded theory analysis derives from in-depth interviews conducted with 24 gay, bisexual, queer, and other men who have sex with men (GBM) living in Toronto, Canada, to understand their experiences of sexual coercion. Participants drew on discourse from the #MeToo movement to reconsider the ethics of past sexual experiences. The idea that gay or queer sex is inherently risky and unique from heterosexual relations made negotiating sexual safety challenging. These notions were enforced by homophobic discourses on the one hand, and counter discourses of sexual liberation, resistance to heteronormativity, hegemonic masculinity, and HIV prevention on the other. Biomedical advances in HIV prevention such as pre-exposure prophylaxis (PrEP) and undetectable viral load affected how some participants felt about sexual autonomy and safety. Participants held themselves responsible for needing to be more assertive within sexual encounters to avoid coercion. Many believed that unwanted sex is unavoidable among GBM: if "you're gay, it's just what happens." Targeted education aimed at GBM communities that incorporates insights on GBM sexual subcultures is necessary. This work must be situated within a broader understanding of how gender norms and hegemonic masculinity, racism, HIV status, and other power imbalances affect sexual decision-making, consent, pleasure, and sexual harm.